(3GdJYhjP ddMGce HCeQ Gddg (B((3aj GdUfYg GdEdgjI(B)s - (3CMeO Hf SYOGddg GdYHGSjs; (3eMeO Hf GdeYR Hf GdefUhQ Hf GdMGce HGeQ Gddgs
(3ChdgG (B:s
(3Chdg HYO GdOjHGLg hPcQ GSe GdLGeY (B: (3gPg fSNI GdJYhjP GdPi cGf ai eYVO GdMGce HCeQ Gddg CejQ GdeDefjf UGMH eUQ s
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B26 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdcjejGA h GdWHjYjGJs